Manajemen Inovasi Pendidikan di Era Digital - Rini, Puput Puspito (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
Educational innovation management in the digital era is a dynamic field of study that integrates educational management, institutional innovation, and digital transformation to transform educational institutions from conventional models to adaptive and competitive ecosystems.This research aims to examine educational innovation management in the digital era through four dimensions: the effectiveness of higher education digital transformation models, the implementation of artificial intelligence in intelligent management systems, digital competency-based curriculum innovation, and the role of specific digital technologies in flexible and responsive learning.The method used is a Systematic Literature Review (SLR) with a rigorous and structured protocol to systematically identify, evaluate, and synthesize scientific evidence to minimize selection bias and produce conclusions that reflect the full range of available empirical evidence.The review of ten articles yielded four main categories: digital transformation of higher education management systems, artificial intelligence and intelligent education management systems, curriculum innovation and student digital competency development, and digital and mobile technology-based learning innovation as strategic instruments.The study concluded that effective digital transformation requires a multidimensional approach with integrated information systems, the integration of artificial intelligence opens up proactive and predictive education governance, technology-based adaptive curriculum innovation produces highly competitive graduates, and the integration of digital technology including mobile creates a more flexible, personalized, and impactful learning experience for the digital generation.